The use of Financial Indicators in Evaluating the Financial Performance of the SAIDAL Company - Maaref, Houda; Naima, Yahiaoui (The journal of contemporary issues in business and government, 2023)
Financial indicators are essential tools for investors and lenders to assess a company’sfinancial performance and ability to meet its financial obligations. This study aims to investigatehow financial indicators can be used to evaluate the financial performance of SAIDAL, a publiclytraded company in Algeria. The study uses data from SAIDAL’s financial statements for the period2018- 2020 to assess the company’s level of financial performance and its ability to use financialindicators to make sound decisions. The study finds that SAIDAL achieved long-term financialstability throughout the study period, as evidenced by its working capital results.